KEBIJAKAN DINAS TENAGA KERJA DAN TRANSMIGRASI DALAM PERLUASAN KESEMPATAN KERJA DI YOGYAKARTA - Bayu Prakoso (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 2006)
The reason behind this research is that there is still problems in limited job opportunities in regency/municipality in Yogyakarta Special Region. The increase of labour force is not yet followed by the increase of job opportunities. The policy made by Dinas Tenaga Kerja dan Trasmigrasi is not yet solving this problem so it cause questions, such as, firstly, what kinds of programmes which have been made by Dinas Tenaga Kerja dan Transmigrasi in each regency/municipality in Yogyakarta Special Region to increase job opportunities. Second, the matchness of job extension programmes in Dinas Tenaga Kerja dan Transmigrasi in Yogyakarta Special Region compare to the labour force.